Quality of life and vital exhaustion among working men and women - Paruzel-Czachura, Mariola (Studia Psychologica: Theoria et praxis, 2013)
The article presents the results of empirical studies about quality of life (Stras-Romanowska, 2007) and vital exhaustion (Kop, Hamulyak, Pernot, Appels, 1998) in the group of working men and women. Research shows that more than half of respondents declare vital exhaustion. The higher level of vital exhaustion occurs among women. The overall result of quality of life is not differentiated by gender and professional activity, but higher scores in the subjective sphere of quality of life occur among entrepreneurs. Workers in state-owned companies have higher level of the metaphysical sphere of quality of life. There is also a negative correlation (r = -0,34; p < 0,01) between quality of life and vital exhaustion.